binomial theorem

Asked by coolameet08 | 10th Feb, 2010, 10:26: AM

Expert Answer:

The second term coefficient in the expasion, is 2n.

The third term coefficient, (2n)(2n-1)/2.

The fourth term coefficient, (2n)(2n-1)(2n-2)/6

fourth term - third term = common difference = third term - second term

(2n)(2n-1)(2n-2)/6 - (2n)(2n-1)/2 = (2n)(2n-1)/2 - 2n

(2n)(2n-1)(2(2n-2)-6)/12 = 2n(2n-1-2)/2

(2n-1)(4n-10)/6 = (2n-3)

(2n-1)(4n-10) - 12n + 18 = 0 

8n2 - 24n + 10 - 12n + 18 = 0

8n2 - 36n + 28 = 0

2n2 - 9n + 7 = 0

Regards,

Team,

TopperLearning.

 

 

 

Answered by  | 14th Feb, 2010, 06:29: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.